Inducing the Growth and Yield of Mungbeans Applied with Different Level of Concentrations of Bio-Stimulant Solutions - Oñal, Jr., Paulino A; Baldonebro, Jessel Jane G.; Cortez, Manuel D.; Andrade, Francis E. (Future Science / FSH-PH Publications, 2024)
The study sought to determine the effects of different levels of concentrations of bio-stimulant solution (BSS) in inducing the growth, flower, and yield of mung bean. The study was conducted at UNO-R School of Agriculture, Philippines last February to April 2022. Pag-asa 3 variety was used as planting material. The study was laid out in RCBD) with four treatments and replicated 4 times. The BSS was diluted in water and applied 6 inches from the base of the plant as per research protocol. Statistical analysis revealed highly significant differences among treatments in growth parameters such as plant height and leaf area index (LAI) at 35DAS. Likewise, there was high significant difference among treatments on the days to 50% flowering of the plant. Furthermore, results showed highly significant differences among treatments in the number of pods per plant, pod weight per plant, number of seeds per pod, 100 seed weight, and yield of mung bean. For the highest plant height, LAI, and period of flowering they were obtained from plants applied with 150ml BSS, followed by 100ml BSS, and 50ml BSS. On the other hand, untreated plants have the shortest height, narrower leaves, and late in flower initiation. Mung bean pods per plant were great in number, heavier in weight from plants treated with 150ml BSS among the other treatments, the most number of seeds per pod, and the heaviest per 100-seed weight as well as the highest seed yield per hectare. This study recommends the use of 150ml BSS in inducing the growth and higher yield of mung bean plant production.